The Role of the Family in the Online Learning System During the Covid-19 Pandemic - Loka, Oktaria Vita; Lian, Bukman; Mahasir, Mahasir (Yayasan Sembilan Pemuda Indonesia, 2022)
In conjunction with schools and teachers, the family plays a significant part in teaching kids how learning should be done. This research seeks to ascertain Family preparation for the teaching strategy the instructor used during the Covid-19 epidemic and the Challenges parents and educators experienced during the Covid-19 pandemic. This research was conducted at SD Negeri 231 Palembang. This research is done using qualitative research. While the research approach or pattern used in this study uses a descriptive research approach pattern. The subjects or sources of data in this study were teachers, non-religious teachers, and parents of students. In this study, there are two sources of data, namely: primary data and secondary data. Researchers use data collection techniques that Interview, Documentation study. Based on the results, of this study SD Negeri 231 Palembang implemented online learning during the Covid-19 pandemic. The role of parents in the Covid-19 pandemic situation has a fundamental position. Moreover, all delivery of material is carried out online and requires technological facilities to be provided to children, so the participation of parents in accompanying their children is very much needed. If in conventional learning the role of parents at home is limited to being parents to their children, in online learning apart from being parents at home, students’ parents also act as educators, mentors, motivators, and facilitators. Obstacles experienced by parents and teachers can be a challenge for parents and teachers by providing appropriate solutions to overcome the obstacles experienced by teachers.